Enteroviral Meningitis: Peculiarities of the Course and Diagnosis at the Present Stage - L.R. Shostakovych-Koretskaya; V.G. Slatvitsky; I.V. Budayeva; Z.O. Chykarenko; L.M. Cherhinets; V.O. Ulianov; O.Y. Lyahova (Zaslavsky O.Yu., 2016)
Background. Enteroviral infection is characterized by a variety of clinical forms: non-specific enterovirus fever, herpangina, hand-foot-and-mouth disease, pleurodynia, meningitis, gastroenteritis, nonspecific enteroviral rash. Enteroviral meningitis is the most urgent clinical form of enteroviral infection, usually with a favorable course and mild to moderate severity. Materials and methods. A retrospective analysis of case histories of 44 children diagnosed with confirmed enteroviral meningitis was performed in this work. Diagnosis of enteroviral meningitis was verified by detection of viral RNA in cerebro-spinal fluid in all patients with polymerase chain reaction method. Age of patients ranged from 3 to 17 years, males and females distribution was close to equal. In addition to routine examinations, in some patients electrocardiography (ECG) was conducted. Results. One-third of patients (n = 10; 30.3 %) showed some changes on ECG, characteristic of myocarditis, in the absence of clinical manifestations of heart disease. This fact points to the need for more careful attention to the diagnosis of mild clinically forms of myocarditis in patients with enteroviral infection that allows recommend the inclusion into the mandatory algorithm of examination of the cardiac pathology with the following activities: conducting ECG studies and research of biochemical cardiac markers (creatine phosphokinase-MB, troponin I, aspartate aminotransferase, alanine transaminase, lactic dehydrogenasefraction). In our study, ECG was performed in 13 patients (39.4 %). Of these, 10 patients (30.3 %) had evidence of heart disease on the ECG with absence of any clinical manifestation suggestive of heart involvement. Conclusions. Epidemiology of enteroviral meningitis preserves its typical features of summer-autumn seasonal pattern, dominant position in the etiological structure of meningitis and most common involvement of pre-pubertate age children (7 to 12 years). In all the observed cases, enteroviral serous meningitis developed in mild to moderate clinical from, without any residuals or mortality. C-reactive protein is a reliable routine criterion for decision of antibiotics prescription. It is recommended to include additional studies (cardiac markers of necrosis, heart ultrasound, ECG) into the mandatory list of examinations when establishing the diagnosis of enteroviral infection.